2015
DOI: 10.1080/00140139.2015.1051595
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the physiological strain and physical burden of chemical protective coveralls

Abstract: This study determined the impact of selected chemical protective coveralls (CPC) on physiological responses and comfort sensations. Fifteen males exercised at approximately 6 METS in three CPC (Tyvek®, Gulf and Tychem®) and a control garment. Physiological strain was characterised by core and skin temperatures, heart rate, V̇O2, perceived exertion, hotness and wetness. Physical burden was characterised by restriction to movement, V̇O2 and RPE. The highest levels of physiological strain and physical burden were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…Contrary to our expectations, no significant differences in the cardiorespiratory variables analyzed between the ensembles were found (Figure 1 ). Previous studies (Baker et al, 2000 ; Dorman and Havenith, 2009 ; Wen et al, 2015 ) reported an increase of 10–20% in the physiological response (e.g., VO 2 ) with the use of different PPC. Other studies (Sköldström, 1987 ; Taylor et al, 2012 ; Lee et al, 2014 ) analyzed a greater increase (>20%) in structure firefighters when they used the self-contained breathing apparatus, due to the rise in weight (10–20 kg) of the ensemble (Lee et al, 2014 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Contrary to our expectations, no significant differences in the cardiorespiratory variables analyzed between the ensembles were found (Figure 1 ). Previous studies (Baker et al, 2000 ; Dorman and Havenith, 2009 ; Wen et al, 2015 ) reported an increase of 10–20% in the physiological response (e.g., VO 2 ) with the use of different PPC. Other studies (Sköldström, 1987 ; Taylor et al, 2012 ; Lee et al, 2014 ) analyzed a greater increase (>20%) in structure firefighters when they used the self-contained breathing apparatus, due to the rise in weight (10–20 kg) of the ensemble (Lee et al, 2014 ).…”
Section: Discussionmentioning
confidence: 94%
“…Gastrointestinal temperature was recorded throughout submaximal trials using a Jonah intestinal temperature capsule (VitalSense, Phillips Respironics, Bend, OR, USA) which was ingested at least 8 h before the beginning of trials (Wen et al, 2015 ). Temperature and humidity underneath the PPC were also measured (Termoregister TR-72U, T and D, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase in core temperature was approximately twice as fast in PPE condition (0.028 ± 0.007°C min -1 ) compared to PPC (0.012 ± 0.004°C min -1 ) or SG (0.011 ± 0.004°C min -1 ). This occurred as a result of the combined effect of the increased metabolic heat production and the heat dissipation limitation associated with the use of PPE, which resulted in a marked situation of uncompensable heat stress ( Table 2 ) and provoked a significantly increased both T gi and T skin ( Figure 2 ) ( Sköldström, 1987 ; Montain et al, 1994 ; Smith et al, 1995 ; Bruce-Low et al, 2007 ; Wen et al, 2015 ; Fontana et al, 2017 ). This fact contributed substantially to reduce the test time to almost half when the subjects wore the PPE.…”
Section: Discussionmentioning
confidence: 99%
“…In total, eight well-defined actions were performed by the participant. Next, fifteen healthy males completed four sessions of walking on a treadmill at 3.5 mph, 4% for 60 minutes in the four clothing ensembles (Wen et al, 2015). Impaired movement was quantified at 5-minute intervals by monitoring the subjective ratings provided by the participants of restriction to their arms and legs and their overall rating of perceived exertion (RPE).…”
mentioning
confidence: 99%